2021
DOI: 10.1002/ece3.7317
|View full text |Cite
|
Sign up to set email alerts
|

Who let the dogs out? Exploring the spatial ecology of free‐roaming domestic dogs in western Kenya

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
16
1
Order By: Relevance
“…HR50 and HR95 of 168 FRDD in seven different areas of Blantyre city, Malawi, and identified factors associated with HR size to better understand how rabies and other dog diseases can spread. Dogs in Blantyre city showed smaller roaming areas than dogs in previous studies where GPS devices were used and the BRB was the HR estimator selected(Dürr et al, 2017;Dürr & Ward, 2014;Hudson et al, 2017;Molloy et al, 2017;Muinde et al, 2021;. Our smaller HR could be partially explained by the lower Hmin used (Mean Hmin = 12.66) compared to that of the studies mentioned (Hmin = 17-20 depending on the study), as HR sizes are sensitive to Hmin value(Dürr & Ward, 2014).…”
contrasting
confidence: 47%
See 3 more Smart Citations
“…HR50 and HR95 of 168 FRDD in seven different areas of Blantyre city, Malawi, and identified factors associated with HR size to better understand how rabies and other dog diseases can spread. Dogs in Blantyre city showed smaller roaming areas than dogs in previous studies where GPS devices were used and the BRB was the HR estimator selected(Dürr et al, 2017;Dürr & Ward, 2014;Hudson et al, 2017;Molloy et al, 2017;Muinde et al, 2021;. Our smaller HR could be partially explained by the lower Hmin used (Mean Hmin = 12.66) compared to that of the studies mentioned (Hmin = 17-20 depending on the study), as HR sizes are sensitive to Hmin value(Dürr & Ward, 2014).…”
contrasting
confidence: 47%
“…Dogs in Blantyre city showed smaller roaming areas than dogs in previous studies where GPS devices were used and the BRB was the HR estimator selected (Dürr et al, 2017; Dürr & Ward, 2014; Hudson et al, 2017; Molloy et al, 2017; Muinde et al, 2021; Warembourg, Wera, et al, 2021). Our smaller HR could be partially explained by the lower Hmin used (Mean Hmin = 12.66) compared to that of the studies mentioned (Hmin = 17–20 depending on the study), as HR sizes are sensitive to Hmin value (Dürr & Ward, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There has also been widespread detection of A. platys in apparently healthy cattle [ 33 , 55 , 64 ]. We speculate that the vector, Rhipicephalus sanguineus , may be feeding on both dogs and cattle in regions where they co-exist, such as in our study region where free-roaming dogs have been observed to frequent poorly managed SHs [ 65 ]. As a result, this dog-tick-cattle cycle can establish a transmission cycle of A. platys that can also potentially involve humans.…”
Section: Discussionmentioning
confidence: 99%